The Effectiveness of Role Playing Learning Model in Improving Students' Understanding of Social Studies Learning at SMP Negeri 24 Surabaya: Efektivitas Model Pembelajaran Role Playing Dalam Meningkatkan Pemahaman Siswa Pada Pembelajaran IPS di SMP Negeri 24 Surabaya - Aziza, Rifky (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2025)
This study was conducted to determine whether or not there is an effect of the use of role-playing learning models on the understanding of class VIII students who are taking social studies lessons. The background of this study is based on the lack of students' understanding of social studies material which is abstract and theoretical, so a more interactive and contextual learning approach is needed. SMP Negeri 24 Surabaya was the location of the research conducted in the 2024/2025 academic year. The study used a quantitative approach with a quasi-experimental model, using the Pretest-Posttest Control Group Design. The research subjects consisted of two classes, namely class VIII-A as the experimental class and class VIII-D as the control class. Data were obtained through understanding tests before and after treatment, which were then analyzed using the independent sample t-test. The results of the analysis showed a significance value (2-tailed) of 0.000 <0.05, which means there was a significant difference between the experimental group and the control group. Thus, it can be stated that the role-playing learning model has proven effective in improving students' understanding of social studies subjects.